New insights into the mechanisms of carbon dioxide mineralization by portlandite. Issue 5 (19th January 2021) - Falzone, Gabriel; Mehdipour, Iman; Neithalath, Narayanan; Bauchy, Mathieu; Simonetti, Dante; Sant, Gaurav
Abstract: Portlandite (Ca(OH)2 ; also known as calcium hydroxide or hydrated lime), an archetypal alkaline solid, interacts with carbon dioxide (CO2 ) via a classic acid–base "carbonation" reaction to produce a salt (calcium carbonate: CaCO3 ) that functions as a low‐carbon cementation agent, and water. Herein, we revisit the effects of reaction temperature, relative humidity (RH), and CO2 concentration on the carbonation of portlandite in the form of finely divided particulates and compacted monoliths. Special focus is paid to uncover the influences of the moisture state (i.e., the presence of adsorbed and/or liquid water), moisture content and the surface area‐to‐volume ratio ( s a / v, mm −1 ) of reactants on the extent of carbonation. In general, increasing RH more significantly impacts the rate and thermodynamics of carbonation reactions, leading to high(er) conversion regardless of prior exposure history. This mitigated the effects (if any) of allegedly denser, less porous carbonate surface layers formed at lower RH. In monolithic compacts, microstructural (i.e., mass‐transfer) constraints particularly hindered the progress of carbonation due to pore blocking by liquid water in compacts with limited surface area to volume ratios. These mechanistic insights into portlandite's carbonation inform processing routes for the production of cementation agents that seek to utilize CO2 borne in dilute (≤30 mol%) post‐combustion flue gas streams.